Managing the screen-viewing behaviours of children aged 5–6 years: a qualitative analysis of parental strategies. Issue 3 (1st March 2016) - Jago, R; Zahra, J; Edwards, M J; Kesten, J M; Solomon-Moore, E; Thompson, J L; Sebire, S J
Abstract : Objectives: The present study used qualitative methods to: (1) examine the strategies that were used by parents of children aged 5–6 years to manage screen viewing; (2) identify key factors that affect the implementation of the strategies and (3) develop suggestions for future intervention content. Design: Telephone interviews were conducted with parents of children aged 5–6 years participating in a larger study. Interviews were transcribed verbatim and analysed using an inductive and deductive content analysis. Coding and theme generation was iterative and refined throughout. Setting: Parents were recruited through 57 primary schools located in the greater Bristol area (UK). Participants: 53 parents of children aged 5–6 years. Results: Parents reported that for many children, screen viewing was a highly desirable behaviour that was difficult to manage, and that parents used the provision of screen viewing as a tool for reward and/or punishment. Parents managed screen viewing by setting limits in relation to daily events such as meals, before and after school, and bedtime. Screen-viewing rules were often altered depending on parental preferences and tasks. Inconsistent messaging within and between parents represented a source of conflict at times. Potential strategies to facilitate reducing screen viewing were identified, including setting screen-viewing limits in relation to specific events, collaborative rule setting, monitoring that involves mothers, fathers and the child, developing a family-specific set of alternative activities to screen viewing and developing a child's ability to self-monitor their own screen viewing. Conclusions: Managing screen viewing is a challenge for many parents and can often cause tension in the home. The data presented in this paper provide key suggestions of new approaches that could be incorporated into behaviour change programmes to reduce child screen viewing.